Handbuch für Preclears - Hubbard, L. Ron (New Era, 2007)
The "Fifteen Acts" of Advanced Procedure and Axioms are paralleled by the fifteen Self-processing Acts given in Handbook for Preclears. Moreover, this book contains several essays giving the most expansive description of the Ideal State of Man. Discover why behavior patterns become so solidly fixed; why habits seemingly can't be broken; how decisions long ago have more power over a person than his decisions today; and why a person keeps past negative experiences in the present. It's all clearly laid out on the Chart of Attitudes - a milestone breakthrough that complements the Chart of Human Evaluation - plotting the ideal state of being and one's attitudes and reactions to life. In self-processing, Handbook for Preclears is used in conjunction with Self Analysis.